Analysis of the Effect of Stock Portfolio Diversification with the Markowitz Method Approach to Portfolio Risk and Return on Idxbumn20 Index Stocks - Refi Tri Anika; Nabila Febriyana; Siti Maisyaroh; Maria Yovita R Pandin (International Journal of Economics and Management Research, 2024)
The purpose of this research is to examine the Effect of Stock Portfolio Diversification with the Markowitz Method Approach to Portfolio Risk and Return on IDXBUMN20 index stocks. This research is a qualitative descriptive research. The subject population consists of 20 stocks of the IDXBUMN20 stock segment listed on the IDX for the period January 2019 to December 2022. IDXBUMN20 contributions from the Indonesia Stock Exchange are used as the main example. at least 4 years. The results of the study show that diversification can increase returns and reduce risks seen in AGRO stocks have a risk of 33% and BRIS 24% with diversification successfully reduced to 19.33% and in ANTM stocks have an expected return of 2.94%, BMRI 1.03% and TINS 0.97% with diversification successfully increased to 3.21%.